Aplication of authenticity criteria in mitochondrial studies on archaic bone remains from a prehispanic Muisca population (2010)
Introduction: Ancient DNA (aDNA)studies can support hypotheses regarding ancient populations; molecular studies can analyze the local population's genetic composition, minimizing biases introduced by later migrations, demographic expansions, mutations, and bottleneck effects. These analyses must be performed with special care because of the low DNA concentrations and contamination risk; therefore, it is necessary to establish protocols to guarantee the reproducibility and veracity of results. Objective: The present study aims to establish a protocol to obtain ancient DNA from 16 pre-Columbian bone samples found in an excavation performed in the area «Candelaria La Nueva» in Bogota, Colombia, dated in the period «Muisca Tardio». Methods: Four founder mitochondrial DNA Amerindian haplotypes were analyzed by high resolution restriction enzyme analyses, obtaining fragments between 121 and 186 base pairs (bp). Different analyses were performed following a strict control of authenticity criteria regarding laboratory conditions, including: positive and negative controls, reproducibility of results, and verification of particular characteristics present in ancient DNA. Results: Results obtained from the bone samples showed the exclusive presence of haplogroup A in the population studied. This data support the statement of the archaeologists of a single biological population in space and time. The distribution of this haplogroup in a 100% frequency supports the hypothesis of Chibcha genetic affiliation. Conclusion: The present study is a contribution to the study of genetic diversity in archaic American populations, allowing the integration of geographic and historic data with genetic characterization techniques associated with linguistic, ethnographic, and glottochronology patterns. Following the protocol proposed in the present study allows fulfilling authenticity criteria for ancient samples with the available techniques. © 2010 Universidad del Valle, Facultad de Salud.